The effect of marketing mix strategies towards customer knowledge and purchase decision on Agromas / Noor A'zizi Omar - Omar, Noor A'zizi (2006)
With an estimated 24 million of consumers, Malaysia has a large market in food production. Malaysia's food sector is changing significantly as lifestyle and traditional eating habit shifting. Although our nation is generally considered to be a price-sensitive market, customers often prefer imported food for both quality and status reasons. However, demand for processed food, both domestic and imported continues to grow and spurred on by successful introduction of numerous new to market products. A part from that, FAMA which one of the government marketing agency offers Malaysian taste product to domestic and abroad customers. Thus, this study on analyzing the effects of marketing mix strategies which consists of the trade events/promotions, promoter effort, taste, packaging and price towards customer knowledge and purchase decision on Agromas Chips and as well as collecting customer feedback in terms of product, promotion, price and perception on the product to determine any area that need further improvement. For primary data, a set of questionnaire has been distributed to the customers who have visited SMIDEC Event 2006 at Sutera Harbour, FAMA Promotion Event at Jin. Kg. Air and Wisma Bandaraya Promotion Event at Wisma Bandaraya. Meanwhile, the secondary data gathered through the internet, articles, newspaper, magazines and books. As for questionnaire have been distributed to the customers, there are several limitations that existed in collecting the information. The results from the finding and analysis can be use as a guideline for FAMA to reach their potential customers. Through the last chapter of this research, it consists of conclusions and recommendations whereas FAMA could think over the suggestion that have been made by customers and researcher.